Panentheism and Theistic Cosmopsychism: God and the Cosmos in the Bhavagad Gītā - Silvestre, Ricardo Sousa (Sophia, 2024)
Panentheism has seen a revival over the past two decades in the philosophical literature. This has partially triggered an interest in Indian models of God, which have traditionally been seen as panentheistic. On the other hand, panentheism has been often associated with panpsychism, an old ontological view that sees consciousness as fundamental and ubiquitous in the natural world and which has also enjoyed a renaissance in recent decades. Depending on where one places fundamentality (whether on the microlevel or on the cosmic-level) there will be two types of panpsychism: micropsychism and cosmopsychism. If we agree on this taxonomy and embrace a panentheistic view which contains the idea of God as the ontologically fundamental entity whose consciousness ontologically supports everything, then panentheism will be considered a kind of cosmopsychism, and consequently a kind of panpsychism (we might term this theistic cosmopsychism.) It is no coincidence then that there has been recent interest within analytic philosophy about the connections between Indian traditions and panpsychism, especially in its cosmopsychist version. My goal in this paper is to contribute to these two debates—the cross-cultural debate over panentheism and Indian models of God, and the connections between cosmopsychism and Indian traditions—by examining one of the most important and often quoted texts in Indian religious and philosophical traditions: the Bhavagad Gītā. From a more specific standpoint, the paper has a threefold goal: to offer a panentheistic reconstruction of the Gītā’s concept of God, to show how this panentheistic model of God entails a form of theistic cosmopsychism, and to locate the Gītā’s cosmopsychism within a broader map of cosmopsychist views. Based on this reconstructive analysis of the Gītā’s cosmopsychism, I also outline some few reflections on the philosophical prospects of theistic cosmopsychism.